2001
DOI: 10.3168/jds.s0022-0302(01)74451-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and Influence of Native, Nonstarter Lactic Acid Bacteria on Cheddar Cheese Quality

Abstract: To determine whether adventitious nonstarter lactic acid bacteria (NSLAB) might affect cheese flavor and quality, we studied a population of NSLAB present in 30 premium quality Cheddar cheeses (3-mo ripened) produced at a commercial facility in the United States. DNA fingerprinting analysis with a sensitive strategy for arbitrary priming polymerase chain reaction showed that 75 isolates corresponded to at least 18 distinct nonstarter organisms. According to ribotype database comparisons of representatives from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 18 publications
7
74
0
3
Order By: Relevance
“…Lactobacillus casei, Lactobacillus paracasei, Lactobacillus plantarum), which constitute the major NSLAB species in Cheddar cheese, have been found to metabolize lactose to compounds (e.g. acetate, galactose) which were not measured in the current study (Jordan and Cogan 1993;Swearingen et al 2001). However, even where lactose was utilized quickly (e.g.…”
Section: Discussionmentioning
confidence: 62%
“…Lactobacillus casei, Lactobacillus paracasei, Lactobacillus plantarum), which constitute the major NSLAB species in Cheddar cheese, have been found to metabolize lactose to compounds (e.g. acetate, galactose) which were not measured in the current study (Jordan and Cogan 1993;Swearingen et al 2001). However, even where lactose was utilized quickly (e.g.…”
Section: Discussionmentioning
confidence: 62%
“…Ong et al (2006) (Karimi et al, 2012b). Several adjunct cultures of strains of the species L. casei and L. plantarum have been claimed to increase peptidolysis and improve the sensory properties of cheese (Lynch et al, 1999;Menéndez et al, 2000;Swearingen et al, 2001;Irigoyen et al, 2007). Escobar et al (2012) reported that probiotic supplementation of Panela Cheese had no effect on perceived taste or appearance and the starchless cheese containing L. rhamnosus GG showed greater consumer acceptance in the compactness, hardness, moisture, and softness descriptors.…”
Section: Pt (Streptococcus Thermophilus + Lactobacillus Plantarum) Rmentioning
confidence: 99%
“…At the same time, NSLAB (whose initial numbers are commonly below 10 2 cfu/g in cheese made under good sanitary conditions with high-quality pasteurized milk) begin to grow and eventually plateau at cell densities of 10 7 to 10 8 cfu/g after 3 to 9 mo of aging (Peterson and Marshall, 1990). Nonstarter LAB populations can be quite diverse, but are usually dominated by facultatively heterofermentative species of lactobacilli (Broome et al, 1990;Fitzsimons et al, 1999;Beresford et al, 2001;Crow et al, 2001;Swearingen et al, 2001;Broadbent et al, 2003).…”
Section: Introductionmentioning
confidence: 99%